2011
DOI: 10.1179/2045772311y.0000000024
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early mortality after cervical spinal cord injury

Abstract: Background: A relatively high early mortality rate (<30 days post-injury) for cervical spinal cord injury (SCI) has been observed. Objective: To investigate this early mortality rate observed after cervical SCI and analyze the associated influential factors. Methods: Medical records for 1163 patients with cervical SCI were reviewed, and the number of patients with early mortality was documented. Through logistic regression analysis, the effects of age, gender, occupation, cause of injury, severity of injury, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 13 publications
4
34
0
Order By: Relevance
“…table; for all online suppl. material, see www.karger.com/doi/10.1159/000382079) [7,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107]. The study duration ranged from less than one year to more than 50 years, and included data beginning in 1935 until 2009.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…table; for all online suppl. material, see www.karger.com/doi/10.1159/000382079) [7,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107]. The study duration ranged from less than one year to more than 50 years, and included data beginning in 1935 until 2009.…”
Section: Resultsmentioning
confidence: 99%
“…Among studies that reported risk of mortality with age at injury, HRs ranged between 1.03 and 3.44 [7,81], and ORs ranged between 1.02 and 1.31 [60,97]. Comparing males to females across studies, HRs ranged between 0.94 and 1.40 [7,77], and ORs ranged between 1.15 and 1.60 [44,58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Injury to the cervical spinal cord accounts for 2 to 3% of trauma patients and 8.2% of all trauma-related deaths. 5 It includes 50 to 75% of all spine injuries. [1][2][3][4][5][6] Suspicion, early diagnosis of injury, preservation of spinal cord function, maintenance or restoration of spinal alignment, and stability are keys to successful management.…”
Section: Introductionmentioning
confidence: 99%
“…5 It includes 50 to 75% of all spine injuries. [1][2][3][4][5][6] Suspicion, early diagnosis of injury, preservation of spinal cord function, maintenance or restoration of spinal alignment, and stability are keys to successful management. Approximately 12,000 new cases (40 cases/million) are added every year to the existing 0.3 to 0.5 million victims in the United States.…”
Section: Introductionmentioning
confidence: 99%